2022
DOI: 10.3390/bioengineering9110668
|View full text |Cite
|
Sign up to set email alerts
|

A Transwell-Based Vascularized Model to Investigate the Effect of Interstitial Flow on Vasculogenesis

Abstract: Interstitial flow plays a significant role in vascular system development, mainly including angiogenesis and vasculogenesis. However, compared to angiogenesis, the effect of interstitial flow on vasculogenesis is less explored. Current in vitro models for investigating the effect of interstitial flow on vasculogenesis heavily rely on microfluidic chips, which require microfluidic expertise and facilities, and may not be accessible to biological labs. Here, we proposed a facile approach to building perfusable v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…It also provides a specific mechanical environment necessary for the physiological activity of interstitial cells . In angiogenesis chips, researchers have predominantly used such devices to introduce and regulate interstitial flow into their culture system with the aim of better understanding endothelial cell behavior. , Deng et al demonstrated that the coculture of HUVECs and NHLFs under interstitial flow promoted lumenization and perfusability of engineered vasculature, enhanced vascular permeability, and stimulated morphogenesis without the need for additional VEGF . Interstitial flow has been demonstrated to upregulate matrix metalloproteinase-2 (MMP-2) and promote neovessel formation, demonstrating enhanced vessel formation, connectivity, and function in the brain microvasculature network .…”
Section: Physical Microenvironmental Cues Affecting Angiogenic Sproutingmentioning
confidence: 99%
See 1 more Smart Citation
“…It also provides a specific mechanical environment necessary for the physiological activity of interstitial cells . In angiogenesis chips, researchers have predominantly used such devices to introduce and regulate interstitial flow into their culture system with the aim of better understanding endothelial cell behavior. , Deng et al demonstrated that the coculture of HUVECs and NHLFs under interstitial flow promoted lumenization and perfusability of engineered vasculature, enhanced vascular permeability, and stimulated morphogenesis without the need for additional VEGF . Interstitial flow has been demonstrated to upregulate matrix metalloproteinase-2 (MMP-2) and promote neovessel formation, demonstrating enhanced vessel formation, connectivity, and function in the brain microvasculature network .…”
Section: Physical Microenvironmental Cues Affecting Angiogenic Sproutingmentioning
confidence: 99%
“… 90 , 143 Deng et al demonstrated that the coculture of HUVECs and NHLFs under interstitial flow promoted lumenization and perfusability of engineered vasculature, enhanced vascular permeability, and stimulated morphogenesis without the need for additional VEGF. 144 Interstitial flow has been demonstrated to upregulate matrix metalloproteinase-2 (MMP-2) and promote neovessel formation, demonstrating enhanced vessel formation, connectivity, and function in the brain microvasculature network. 145 In brain microvasculature models, Winkleman et al described the role of interstitial pressure by devising a simple 3-channel microfluidic system comprising primary brain ECs, pericytes, and astrocytes within a 3D fibrin matrix.…”
Section: Physical Microenvironmental Cues Affecting Angiogenic Sproutingmentioning
confidence: 99%